Pengaruh Literasi Digital terhadap Kemampuan Memahami Teks pada Siswa Sekolah Menengah - Sitti Nur Aisyah; Fitra Novilani; Ainun; Anita Candra Dewi (AIJER: Algazali International Journal Of Educational Research, 2025)
This study analyzes the influence of digital literacy on the ability to understand texts in secondary school students using a descriptive qualitative approach with a literature study method. The results of the study indicate that digital literacy has a positive and significant impact on improving students' ability to understand texts. The implementation of technology such as the Picture and Picture method and the use of QR Codes have proven effective in increasing students' interest, involvement, and skills in analyzing and interpreting texts. Digital literacy not only strengthens literal understanding of texts but also develops critical and creative thinking skills needed to evaluate information in the digital era. A structured digital learning strategy with stages of prediction, discussion, explanation, observation, and reflection shows better learning outcomes than conventional methods. This study emphasizes the importance of integrating digital literacy into the secondary education curriculum to prepare students to face the challenges of information in today's technological era.